Dinuclear copper(II) complexes containing 6-(benzylamino)purines as bridging ligands: synthesis, characterization, and in vitro and in vivo antioxidant activities - Starha, Pavel; Trávnícek, Zdenek; Herchel, Radovan; Popa, Igor; Suchý, Pavel; Vanco, Ján (Journal of inorganic biochemistry, 2009)
A series of dinuclear copper(II) complexes involving 6-(benzylamino)purine derivatives, (HL(n)), as bridging ligands were synthesized, characterized and tested for both their in vitro and in vivo antioxidant activities. Based on results of elemental analyses, temperature dependence of magnetic susceptibility measurements, UV-vis, FTIR, EPR, NMR and MALDI-TOF mass spectroscopy, conductivity measurements and thermal analyses, the complexes with general compositions of [Cu(2)(mu-HL(n))(4)Cl(2)]Cl(2).2H(2)O (1-4) and [Cu(2)(mu-HL(n))(2)(mu-Cl)(2)Cl(2)] (5-7) were prepared {where n=1-4; HL(1)=6-[(2-methoxybenzyl)amino]purine, HL(2)=6-[(4-methoxybenzyl)amino]purine, HL(3)=6-[(2,3-dimethoxybenzyl)amino]purine and HL(4)=6-[(3,4-dimethoxybenzyl)amino]purine}. In the case of complexes 2, 3, 5 and 7, the antioxidant activities were studied by both in vitro {superoxide dismutase-mimic (SOD-mimic) activity} and in vivo {cytoprotective effect against the alloxan-induced diabetes (antidiabetic activity)} methods. The obtained IC(50) value of the SOD-mimic activity for the complex 5 (IC(50)=0.253 microM) was shown to be even better than that of the native bovine Cu,Zn-SOD enzyme (IC(50)=0.480 microM), used as a standard. As for the antidiabetic activity, the pretreatment of mice with complexes 3 and 7 led to the complete elimination of cytotoxic attack of alloxan and its free radical metabolites, used as a diabetogenic agent. The cytoprotective effect of these compounds was proved by the preservation of the initial blood glucose levels of the pretreated animals, as against the untreated control group.
Keywords: benzylové sloučeniny; Purines; antioxidancia; Copper; experimentální diabetes mellitus; Kinetin; cytoprotekce; puriny; Cytoprotection; Benzyl Compounds; hypoglykemika; Animals; Antioxidants; zvířata; myši; Hypoglycemic Agents; Diabetes Mellitus, Experimental; měď; Superoxide Dismutase; Mice; superoxiddismutasa; kinetin